Remarks by World Bank Group President David Malpass on World Environment Day 2022 - Mobilizing Communities for Sustainability : The Role of the Indian State - Malpass, David (World Bank, Washington, DC, 2022)
These were the remarks delivered by World Bank Group President David Malpass on World Environment Day 2022 about Mobilizing Communities for Sustainability : The Role of the Indian State on June 5, 2022. He said that on the occasion of the world’s environment day and in honor of Prime Minister Modi’s focus on Lifestyle for the Environment (LiFE) and his call for papers, he was guided to the ancient texts of India and enlightened by their great respect for the natural world and the environment. He focused on the question of what the state can do to mobilize communities at scale for sustainable economic growth and development. He mentioned that localizing decisions to the community level has been an important part of India’s development philosophy. He highlighted on getting prices right remains a vital prerequisite for changing behaviors of communities and strengthening the economy. He said that getting institutions right is also a vital prerequisite. He mentioned that alongside community motivators, mobilizing communities around development and climate-related issues will require more effective local governments and local administration. He said that to help support change, India has an impressive system of cash and non cash transfers that forms the foundation of a strong social protection system using a unique ID mechanism. He also added that it is vitally important, the state must get pricing policies and institutions right in order to credibly invite communities to participate in development programs as part of a mass movement. He said that they look forward to supporting this with a whole of World Bank approach combining the full resources and energy of the IBRD, IDA, IFC and MIGA. He highlighted that call for papers offers the opportunity to use scholarly work to understand better how policies and institutions matter in incentivizing and leveraging communities around development issues. He concluded by saying that let us not lose this learning opportunity being offered here that day by Prime Minister Modi, who said recently that once people are determined to do something together, they do wonderful things.